Formulasi Model Inovasi Edu-Ecotourism Berbasis Analisis Potensi Ekowisata Di Desa Wisata Penglipuran Bali - Pasha, Aldriaza Davhin; Sitanggang, Igras Vigran Antonio; Dira Oktavia, Reno Catelya (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2068, 2026)
This study aims to analyze the ecotourism potential of Penglipuran Tourism Village, Bali, as the basis for formulating the Integrated Edu-Ecotourism Innovation Framework (IEIF) to support sustainable tourism development. The study employed a descriptive-evaluative research design using a combination of quantitative and qualitative approaches. Ecotourism potential was assessed through field observations, documentation, and evaluation of existing conditions using the Avenzora indicators with the one score one criteria approach and a seven-point Likert scale. The findings indicate that Penglipuran Tourism Village possesses high ecotourism potential, particularly in the dimensions of spirituality (6.69), green open spaces (6.57), flora (6.51), fauna (6.52), tangible and intangible cultural heritage (>6.25), souvenirs (6.64), and culinary resources (6.61). In contrast, natural phenomena received the lowest score (5.29), highlighting the need for strategic enhancement as part of destination development. Based on these findings, the IEIF model was developed by integrating product innovation through digital-based educational trails, process innovation through carrying capacity management and zoning regulations, and management innovation through the establishment of a community-based edutourism hub supported by a continuous feedback loop mechanism. This study concludes that the IEIF model effectively integrates natural and cultural resources as the foundation for sustainable edu-ecotourism development. Keywords : edu-ecotourism, ecotourism potential, tourism village, destination innovation